Strategies and mechanisms of resistance to viruses in photosynthetic aquatic microorganisms (Advances in Oceanography and Limnology, 2012)
Surviving viral attack is essential for any species to avoid its irreversible removal from the ecosystem, and microbes must involve the resistance or susceptibility of individual cells. The co-existence between viruses and their hosts has led to the evolution of complex viral attack and host defence strategies. We review the state of the art about our understanding of resistance to viruses in aquatic eukaryotic photosynthetic microorganisms for which no synthesis has been provided yet, with comparisons to what is known for (cyano)bacteria or archaea. We discuss the cost of viral resistance to host cells, pointing out why it is important to consider its effect in studies of aquatic ecosystems, and how this may lead to a better understanding of population growth, structure, succession and blooms. The evolutionary consequences of resistance in the host-virus interactions are then reviewed, before considering possible perspectives for future research.
Keywords: Resistance; plankton; viruses; aquatic ecosystems